Wise education in the use of gadgets - Ratnadewi Ratnadewi; Olga Catherina Pattipawaej; Ria Wardani; Ida Ida; Ariesa Pandanwangi (Universitas Muhammadiyah Magelang, 2023)
Advances in technology have made it impossible for everyone to avoid using gadgets. The devices used are varied, ranging from mobile phones, computers, laptops, etc. Social media applications used are various types and are very applicable. Device users are not only from workers, but children and adolescents are using it. Social media contains educational content, skills, hobbies, entertainment, and adult content. The problems are some children often choose adult shows and the time spent using the device often escapes parental supervision. The purpose of this program is to transfer knowledge regarding solutions in using devices using the service learning (SL) method. Device use in children and early adolescents needs to be regulated starting from the time of use, supervision, purpose, accessible content, and where to use the device. The results of community service are that the role of parents and family is very important in educating young children and adolescents in using gadgets wisely, children understand the limitations of using devices from the length of time they are used, places, and materials that can be seen.